Investigaciones sobre el picudo del frijol, la mustia hilachosa y el mosaico dorado en Centroamerica y Mexico - Gálvez E., Guillermo E. (International Center for Tropical Agriculture, 1982)
Advances in research conducted by the Centro Internacional de Agricultura Tropical together with its technicians in Central America, and the close collaboration with national programs are analyzed regarding factors limiting bean productivity in Central America: the bean pod weevil (Apion godmani), BGMV, and web blight (Thanatephorus cucumeris). A total of 28 bean pod weevil-resistant lines have been obtained in which the percentage of damaged seeds and pods was reduced by 72 and 42 percent, resp. Lines Bat 1235, BAT 1230, Porrillo 70, S-603B, and Porrillo 1 have showed tolerance to web blight in trials in international nurseries (Colombia, Panama, Costa Rica, Nicaragua, El Salvador, Guatemala, and Mexico). Since this tolerance is not sufficient to control the disease, studies have been conducted on chemical and cultural control. The use of mulches combined with a min. tillage system and the use of postemergence herbicides is the most significant practice to obtain an efficient control. With this integrated control system yields up to 1500 kg/ha have been obtained with ICA-Palmar in Panama compared with 500 kg/ha when this system is not used. BGMV-tolerant lines have been released; in Preliminary Trials in 1981 2 tolerant lines were recorded: A171 and A174. (CIAT)